Building trust in elementary schools: the impact of home school community collaboration - Ho Sui Chui, Esther (International Journal about Parents in Education, 2023)
There is a general consensus among contemporary social scientists that social trust is important(Alexander, 2003; Coleman, 1990; Delhey & Newton, 2003; Huang, 2003; Putnam, 1993). In thecontext of education, trust was seen as a goal and a tool for school improvement (Meier, 2002; Brown, 1998; Schneider & Bryk, 2002). This paper examines teachers’ trust in schools and the factors related to their level of trust. Results of factor analysis show that 19 items measuring teachers’ trust can be categorized into four factors of relational trust: “teachers trust on students”; “parents trust on teachers”; “teachers trust on parent” and “teachers trust on parental involvement”. Results from descriptive analysis indicated that teachers in general hold a positive attitude toward the students and their parents, and majority of teachers are also quite positive towards parents’ support and the mutual respect between teacher and parents in Hong Kong. Results from the hierarchical regression analysis suggested that parent social background factors (SES), but not teachers’ background factors, has the strongest association with teachers’ level of trust. The results suggested that upper-class students are more likely to have higher level of trust on student, trust on parent and trust on parental involvement. However, teachers are more likely work harder to establish trust relationship with parents from working class students. Moreover, the seven types of home-school-community collaboration appears to have different contribution to the dimensions of relational trust in Hong Kong elementary schools even after background factors have taken into account.